THE AGE OF THE BARABA FORMATION INFERRED FROM THE U/PB (SHRIMP) DATING (SREDINNYI RANGE, KAMCHATKA): GEOLOGICAL CONSEQUENCES - Soloviev A.V.; Grigorenko E.S.; Hourigan J.K.; Brandon M.T.; Garver J.I. (My University, 2004)
The Baraba Formation exposed in the Sredinnyi Range (Kamchatka), where it is composed of ter- restrial conglomerates, was considered for a long time as the late Campanian-lower Maastrichtian in age based on the fossil flora evidence. Zircons from the tuff layer in the lower part of the formation are dated at 50.5 ± 1.2 Ma using the U/Pb (SHRIMP) method, i.e., the accumulation of their host deposits commenced in the ter- minal early Eocene. The Baraba Formation overlies unconformably schists and phyllites of the Malka Group, which were metamorphosed during the pre-middle Eocene time, and the Irunei marginal-sea sediments thrust over metamorphic complexes and thus suggesting the pre-middle Eocene thrusting stage.